ORDER OF MORPHEMES ACQUIRED BY THE FIRST SEMESTER STUDENTS OF ENGLISH DEPARTMENT AT THE FACULTY OF EDUCATION - Lumban Raja, Viator (Kairos English Language Teaching Journal, 2017)
This research is pertinent to the morphemes made in the writing examination by the first semesterÂ students or freshman of English Department of Faculty of Education Catholic University of SaintÂ Thomas in the academic year 2012/2013. There are two classes of the first semester students in EnglishÂ Department, and one class with 34 students is taken out as a sample to represent the whole first semesterÂ students in the academic year 2012/2013. The research data is taken from the result of the first semesterÂ writing examination, especially paragraph writing. Thus, there are 34 paragraphs thoroughly examinedÂ one by one to obtain morphemes both inflectional and derivational morphemes, including compounding words. The result of data analysis shows that the students produce 550 morphemes comprising 450Â inflectional morphemes, 100 derivational morphemes, and 20 compounding words. Of the inflectionalÂ morphemes, irregular past morpheme amounts to 169, and that of regular one amounts to 101. But if itÂ is seen from the verb form without the frequencies, the regular verb form amounts to 59 verbs, while the irregular amounts to 36 verbs only. In other words, the irregular verb form has much moreÂ frequencies than that of the regular one. Then, this number is followed by the plural morpheme whichÂ amounts to 77 frequencies. Meanwhile, of the derivational morphemes, noun suffix -ing has theÂ highest position, namely 57 frequencies, then followed by adjective with 28 frequencies, adverb with 15 frequencies and verb with 1 frequency. Based on the data analysis, it can be concluded that the easiestÂ morphemes are the most produced by the students, and then followed by the most difficult morphemes.Â This is in line with the language learning theory which says that the learners will grasp the easiest partsÂ first, then gradually move to the more difficult.